Counteracting Action of Curcumin on High Glucose-Induced Chemoresistance in Hepatic Carcinoma Cells - Soni, Vivek Kumar; Mehta, Arundhati; Ratre, Yashwant Kumar; Chandra, Vikas; Shukla, Dhananjay; Kumar, Ajay; Vishvakarma, Naveen Kumar (Frontiers in Oncology, 2021)
Along with direct anticancer activity, curcumin hinders the onset of chemoresistance. Among many, high glucose condition is a key driving factor for chemoresistance. However, the ability of curcumin remains unexplored against high glucose-induced chemoresistance. Moreover, chemoresistance is major hindrance in effective clinical management of liver cancer. Using hepatic carcinoma HepG2 cells, the present investigation demonstrates that high glucose induces chemoresistance which is averted by the simultaneous presence of curcumin. Curcumin obviated the hyperglycemia-induced modulations like elevated glucose consumption, lactate production, and extracellular acidification, and diminished nitric oxide and reactive oxygen species (ROS) production. Modulated molecular regulators are suggested to play a crucial role as curcumin pretreatment also prevented the onset of chemoresistance by high glucose. High glucose instigated suppression in the intracellular accumulation of anticancer drug doxorubicin and drug-induced chromatin compactness along with declined expression of drug efflux pump MDR-1 and transcription factors and signal transducers governing the survival, aggressiveness and apoptotic cell death (p53, HIF-1α, mTOR, MYC, STAT3). Curcumin alleviated the suppression of drug retention and nuclear condensation along with hindering the high glucose-induced alterations in transcription factors and signal transducers. High glucose-driven resistance in cancer cells was associated with elevated expression of metabolic enzymes HKII, PFK1, GAPDH, PKM2, LDH-A, IDH3A, and FASN. Metabolite transporters and receptors (GLUT-1, MCT-1, MCT-4, and HCAR-1) were also found upregulated in high glucose exposed HepG2 cells. Curcumin inhibited the elevated expression of these enzymes, transporters, and receptors in cancer cells. Curcumin also uplifted the SDH expression which was inhibited in high glucose condition. Taken together, the findings of the present investigation first time demonstrate the ability of curcumin against high glucose-induced chemoresistance, along with its molecular mechanism. This will have implication in therapeutic management of malignancies in diabetic conditions.